2012
DOI: 10.1016/j.jmr.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Phase-contrast MRI and CFD modeling of apparent 3He gas flow in rat pulmonary airways

Abstract: Phase-contrast (PC) magnetic resonance imaging (MRI) with hyperpolarized 3He is potentially useful for developing and testing patient-specific models of pulmonary airflow. One challenge, however, is that PC-MRI provides apparent values of local 3He velocity that not only depend on actual airflow but also on gas diffusion. This not only blurs laminar flow patterns in narrow airways but also introduces anomalous airflow structure that reflects gas-wall interactions. Here, both effects are predicted in a live rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Airflow 17,18,32 and particle deposition 13,25,35 in the lung were shown to be highly dependent on geometry and flow asymmetry 8 . Boundary conditions that describe the upstream and downstream mechanics outside of the 3D domain must be defined on the inlets and outlets for all CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Airflow 17,18,32 and particle deposition 13,25,35 in the lung were shown to be highly dependent on geometry and flow asymmetry 8 . Boundary conditions that describe the upstream and downstream mechanics outside of the 3D domain must be defined on the inlets and outlets for all CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, constant pressure 17 or flow rate 11,26 boundary conditions have been applied at the mouth or trachea. Constant pressure 17,26,46 or flow rate 11,32 boundary conditions are typically implemented at the distal airway outlets. However, as the flow patterns change in time, CFD simulations should model the breathing unsteadiness, to determine airflow 30 and particle 13 deposition patterns in the lung.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, airflow measurement with PCV MRI has been performed in human airways with 3 He in a single axial slice of the trachea using a radial sequence (10). More recently, Minard et al (11) measured velocity fields in rat pulmonary airways with a 3D radial sequence, HP 3 He and an acquisition time of 14 min. Similar to 3 He, HP 129 Xe can also be used as a tracer gas for lung MRI (12) and PCV-MRI in vitro (13) and in vivo (14).…”
Section: Introductionmentioning
confidence: 99%
“…The influences of tidal breathing [30,31,32], dynamic airways [33,34,35,36], polydisperse aerosols [37,38], hygroscopic growth [39,40,41], electric charges [42,43], and intersubjective variability [44,45,46] on acrolein deposition are also important and should be considered in future studies. Imaging techniques such as phase-contrast MRI (magnetic resonance imaging) with hyperpolarized 3 He can be used to visualize respiratory flows [47,48]. It is acknowledged that MD and CFD simulations were conducted separately, without coupling, in this study, as two distinct methods for understanding the experimentally observed concentration-dependent acrolein deposition in rats.…”
Section: Discussionmentioning
confidence: 99%